The Effectiveness of Using Flashcards on Students’ Writing Skills in Descriptive Texts - Mia Ernika Samosir; Fiber Yun Almanda Ginting; Jenita Anjani Br. Sembiring (Jurnal Educatio FKIP UNMA, 2026)
Writing is one of the essential language skills that students need to master; however, many junior high school students still face difficulties in generating ideas, organizing sentences, and using appropriate vocabulary in descriptive writing. To address these problems, flashcards were used as a visual learning medium to facilitate students’ writing activities. This study aimed to determine the effect of using flashcards on students’ writing skills in descriptive texts. The research employed a quantitative approach with a quasi-experimental design. The participants were 66 seventh-grade students of SMP Deli Murni in the 2025/2026 academic year, consisting of 33 students in the experimental class and 33 students in the control class. The instrument used to collect the data was a writing test administered through pre-test and post-test. The students’ writing was assessed based on content, organization, vocabulary, language use, and mechanics. The data were analyzed using descriptive statistics, normality and homogeneity tests, paired sample t-test, and independent sample t-test. The findings revealed that the students who were taught by using flashcards showed greater improvement in writing descriptive texts than those who were taught through conventional methods. The mean score of the control class increased from 45.70 to 67.82, while the experimental class improved from 48.94 to 78.76. Furthermore, the independent sample t-test showed a significance value lower than 0.05, indicating that flashcards had a significant effect on students’ writing skills. Therefore, it can be concluded that flashcards are effective in improving students’ ability to write descriptive texts.